High resolution computed tomography chest findings during admission and follow-up in severe COVID-19 infection - Puri, Niraj; Adhikari, Shital; Bhattarai, Madhur Dev; Gauli, Basanta; Gurung, Sailesh; Patel, Sunil; Wagley, Pratik; Adhikari, Deepak; Paudel, Bigyan (Journal of Chitwan Medical College, 2022)
Background: The full extent of pulmonary damage and long-term prognosis due to severe COVID-19 pneumonia is still unclear. This study was aimed to characterize and compare changes in the radiological pattern of HRCT chest in severe COVID-19 pneumonia patients from admission to that of follow-up. Methods: This was a one-year prospective study done at Chitwan Medical College from April 2020 to April 2021. Total 56 patients with severe COVID-19 pneumonia who had at least one HRCT chest during admission and another during follow-up within 5 weeks. Based on the total number of days on systemic steroids, patients were separated into three follow-up groups. Statistical Package for Social Science version 20 was used for data input and descriptive analysis. Point estimate at 95% Confidence interval was calculated along with frequency and descriptive statistics. Results: The median CT severity index scores of follow-up HRCT chest improved from 14.5 to 10.0 in the 3rd week and from 16.0 to 11.5 in the 5th week. Ground Glass Opacity resolved early and steadily. The prevalence of bronchiectasis and fibrosis was considerable, with no meaningful improvement up to 5th week. Conclusions: Significant radiological improvement can be seen as early as 3rd week from recovery phase of severe COVID-19 pneumonia where systemic steroids have a key contributory role. High frequency of bronchiectasis and fibrosis from in-patient HRCT chest may be due to acute COVID-19 pneumonia lesions on the preexisting undiagnosed lung diseases which may be falsely ascribed to the post-COVID.